English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Prove the identity: tan x - 1/ tan x + 1 = 1 - cot x/ 1 + cot x

2006-09-27 16:03:42 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

If we assume tanx=y
==> cotx=1/y
==>(y-1)/(y+1)=(1-1/y)/(1+1/y)
1-1/y=(y-1)/y
1+1/y=(y+1)/y
==>
(1-1/y)/(1+1/y)=
((y-1)/y)/((y+1)/y)
((y-1)*y)/((y+1)*y)
=(y-1)/(y+1)
so both sides are equal

2006-09-29 22:10:40 · answer #1 · answered by Mamad 3 · 0 0

you mean (tan x-1)/(tan x+1) = (1-cot x)/(1+cot x)
lhs
= (1/cot x - 1)/(1/cot x + 1)
= ((1-cotx)/cotx)/((1+cot x)/cotx))
= (1-cot x)/(1+cot x)
= rhs
proved

2006-09-30 03:09:54 · answer #2 · answered by Mein Hoon Na 7 · 0 0

per chance i'd be able to get you all started my innovations are frequently for algebra its merely that likely I see something (a million+tanx) / (a million+cotx) = (a million-tanx) / (cotx-a million) the right denominator a million/(cotx-a million)=a million/(-a million+cotx)= -a million/(a million-cotx) so (a million-tanx)/(cotx-a million)= -(a million-tanx)/(a million-cotx) will provide you (a million+tanx) / (a million+cotx)= -(a million-tanx)/(a million-cotx) you could now make the denominators into 'replace of squares' left element (a million+tanx)/(a million+cotx)*(a million-cotx)/(a million-cotx)=(a million..... incredible side -(a million-tanx)/(a million-cotx)*(a million+cotx)/(a million+cotx)= -(a million-tanx)(a million+cotx)/(a million-cotx^2) the (a million-cotx^2)'s cancel leaving (a million+tanx)(a million-cotx)= -(a million-tanx)(a million+cotx) likely you could take it from there? maximum proper reliable fortune

2016-12-06 07:02:37 · answer #3 · answered by ? 3 · 0 0

ya right do your own homework

2006-09-27 16:05:37 · answer #4 · answered by maxi 4 · 0 1

fedest.com, questions and answers